Analisis Pengelolaan Daerah Aliran Sungai Terpadu Terhadap Pengurangan Risiko Bencana - Nabila, Nabila (WBS Laboratory, 2025)
Integrated Watershed Management (DAS) is a holistic approach to managing natural resources, reducing disaster risk, and increasing environmental resilience. This study aims to analyze the effectiveness of integrated watershed management in reducing disaster risk in Indonesia. The analysis methods include literature review, policy evaluation, hydrological and environmental data analysis, and participatory studies involving various stakeholders. The results of the analysis indicate that integrated watershed management has a significant role in mitigating natural disasters such as floods, landslides, and droughts. Steps such as vegetation conservation, erosion control, land use regulation, and active community participation have helped reduce disaster risk in a number of watersheds in Indonesia. Several challenges that need to be overcome in the implementation of integrated watershed management include lack of coordination between institutions, limited resources, and low public awareness of the importance of environmental conservation. Therefore, further efforts are needed to improve institutional capacity, strengthen collaboration between institutions, and increase community participation in integrated watershed management. This study provides deeper insight into the role of integrated watershed management in reducing disaster risk in Indonesia, as well as providing recommendations for further improvement and development in disaster mitigation efforts at the watershed level.